Spin orientation of the Galilean satellites - Yseboodt, M. (2025)
The Galilean satellites are locked in a 1:1 spin-orbit resonance. Their rotation axis is assumed to be in a Cassini state and to follow the long-term precession of the orbit normal. The obliquity, which is the angular separation between the rotation axis and the orbit normal, is expected to be small.